S3 guideline "actinic keratosis and cutaneous squamous cell carcinoma" - update 2023, part 1: treatment of actinic keratosis, actinic cheilitis, cutaneous squamous cell carcinoma in situ (Bowen's disease), occupational disease and structures of care: guideline - Heppt, Markus V.; Leiter, Ulrike; Steeb, Theresa; Alter, Mareike; Amaral, Teresa; Bauer, Andrea; Bechara, Falk G.; Becker, Jürgen C.; Breitbart, Eckhard W.; Breuninger, Helmut; Diepgen, Thomas; Dirschka, Thomas; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2023)
Actinic keratosis (AK) are common lesions in light-skinned individuals that can potentially progress to cutaneous squamous cell carcinoma (cSCC). Both conditions may be associated with significant morbidity and constitute a major disease burden, especially among the elderly. To establish an evidence-based framework for clinical decision making, the guideline “actinic keratosis and cutaneous squamous cell carcinoma” was updated and expanded by the topics cutaneous squamous cell carcinoma in situ (Bowen's disease) and actinic cheilitis. The guideline is aimed at dermatologists, general practitioners, ear nose and throat specialists, surgeons, oncologists, radiologists and radiation oncologists in hospitals and office-based settings, as well as other medical specialties, policy makers and insurance funds involved in the diagnosis and treatment of patients with AK and cSCC. A separate guideline exists for patients and their relatives. In this part, we will address aspects relating to AK, actinic cheilitis, Bowen's disease, occupational disease and care structures.
Gesehen am 07.10.2024